The role of sport-specific play and practice during childhood in the development of adolescent Finnish team sport athletes - Forsman, H.; Blomqvist, M.; Davids, K.; Konttinen, N.; Liukkonen, J. (International Journal of Sports Science & Coaching, 2016)
This study sought to understand the role of sport-specific play and practice in the development of adolescent team sport athletes in the Finnish sports development system. Participants were male, 15-year-old soccer (n=141), ice hockey (n=204), and basketball (n=96) players, divided into three groups based on the amount of sport-specific play and practice experienced during childhood. Data were collected with sport-specific inventories of practice history, tactical skills, psychological skills, and sport-specific skill test. Results showed that athletes with more sport-specific play and practice during childhood had more sport-specific play and practice during adolescence, better technical, tactical, and psychological skills, and were more likely to be selected for national youth teams at the age of 15. Data highlighted the importance of sport-specific play and practice during childhood in the development of team sport performers in the Finnish athlete development system.